2021
DOI: 10.47162/rjme.62.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Atypical posterior circulation strokes: a case-based review of rare anatomical variations involved

Abstract: The circle of Willis is a very important vascular mechanism of protecting against cerebral ischemia, especially when circulation within the main arteries irrigating the brain is somehow impeded. As result of congenital malformation arising early in embryonic development, the fetal-type posterior circle of Willis remains as such during the rest of one's life. Consequently, the posterior cerebral artery (PCA) becomes a branch of the internal carotid artery (ICA), rather than of the basilar artery (BA). Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…At a gestational age of about 5 weeks (from the 4mm to 12-mm embryo stage), the cerebral arterial circle formed by the carotid system and followed by the posterior circulation (Luh et al, 1999). As the posterior cerebrum, cerebellum and brainstem grow, the posterior circulation develops from the primitive arterial mesh, longitudinal neural arteries (Lambert et al, 2016;Roman-Filip et al, 2021). Although the caudal internal carotid artery regresses becoming the posterior communicating artery in typical cerebral arterial circle, it might continue to be dominant and becomes the fetal-type variant of the PCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a gestational age of about 5 weeks (from the 4mm to 12-mm embryo stage), the cerebral arterial circle formed by the carotid system and followed by the posterior circulation (Luh et al, 1999). As the posterior cerebrum, cerebellum and brainstem grow, the posterior circulation develops from the primitive arterial mesh, longitudinal neural arteries (Lambert et al, 2016;Roman-Filip et al, 2021). Although the caudal internal carotid artery regresses becoming the posterior communicating artery in typical cerebral arterial circle, it might continue to be dominant and becomes the fetal-type variant of the PCA.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cases of concurrent manifestation of cerebral infarction and fetal-type variant of the PCA have been reported. Fetal-type variant of the PCA was concurrently observed with ipsilateral multiple (middle cerebral artery and PCA) infarctions with stenotic internal carotid artery without known etiology (Kolukısa et al, 2015), with ipsilateral multiple (anterior cerebral artery, middle cerebral artery, and PCA) infarctions or with contralateral multiple (middle cerebral artery and PCA) infarctions (Lambert et al, 2016), and with thalamic infarction (Roman-Filip et al, 2021). Yang et al (2007) reported that the fetal-type variant of the PCA was more frequently found in the ipsilateral hemisphere of patients with an infarction than in the control group (44.4 % vs 18.5 %) by both diffusion-weighted magnetic resonance imaging (DWI) and cerebral angiography (1388 patients), of which large artery atherosclerosis of the carotid artery was very common in patients with infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The embryological classification of the variants of midbrain drainage consists of three types of possible venous architecture: normal continuous (type A), normal discontinuous (type B) and primitive variant (type C). During embryological development, the basal vein of Rosenthal is formed by the longitudinal fusion of three primitive veins as they initially drain in the tentorial sinuses, but as the development progresses, those vessels start to obliterate as their drainage shifts towards the Galenic system [ 29 , 30 ]. Various failures of anastomosis between first and second primitive veins results in type B and type C drainage, respectively, while type A is considered ideal [ 24 ].…”
Section: Pathogenic Sequence and Causesmentioning
confidence: 99%
“…Because the CoW supplies blood to the brain, in case of occlusion of one of the cerebral arteries, identification of anatomical variants that could be present at this level could be useful in the assessment of stroke (ischemic or hemorrhagic) [10][11][12], especially in the Romanian population, as Romania it situated among the first 10 countries in the world in terms of this morbidity [13].…”
Section:  Introductionmentioning
confidence: 99%
“…In our days, stroke represents one of the greatest challenges of the public health systems as major morphological changes, such as disturbances of the blood–brain barrier, appears in the brain of the affected patients [ 9 ]. Because the CoW supplies blood to the brain, in case of occlusion of one of the cerebral arteries, identification of anatomical variants that could be present at this level could be useful in the assessment of stroke (ischemic or hemorrhagic) [ 10 , 11 , 12 ], especially in the Romanian population, as Romania it situated among the first 10 countries in the world in terms of this morbidity [ 13 ]. Moreover, knowing the prevalence, incidence, and types of anatomical anomalies that could affect the component arteries of the CoW could be useful for the understanding of some psychiatric conditions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%